Students' Science Literacy Ability: Study on the Topic of Environmental Pollution at SMPN 2 Merbau Mataram - Maulina, Dina; Triyaningsih, Fatimah; Yolida, Berti; Cipta, Sayid (Journal of Adaptive Education, 2023)
Scientific literacy is one of the determining factors in preparing competent human resources in the future. This study aimed to determine students' scientific literacy skills based on the PISA framework. This research is ex post facto research, with a crosssectional survey design. The research sample was selected by purposive sampling of 224 students in class VIII SMP Negeri 2 Merbau Mataram. Quantitative data from students' scientific literacy competency scores obtained with PISA questions were then analyzed descriptively. The results of students' scientific literacy competence in this study were in the "very low" category (30.06 ± 1.8). Based on the aspect of scientific competence, identifying scientific problems (33.35 ± 2.58) has the highest score, then using scientific evidence (36.18 ± 3.21), and the lowest score is the aspect of explaining scientific phenomena (20.7 ± 1,7). Thus, the results of this study concluded that students' scientific literacy abilities at SMPN 2 Merbau Mataram were in the very low category.